Yet Another Mitochondrial Genome of the Pacific Cupped Oyster: The Published Mitogenome of Alectryonella plicatula (Ostreinae) Is Based on a Misidentified Magallana gigas (Crassostreinae) - Salvi, Daniele; Berrilli, Emanuele; Garzia, Matteo; Mariottini, Paolo (Frontiers in Marine Science, 2021)
The recently published mitochondrial genome of the fingerprint oyster Alectryonella plicatula (Gmelin, 1791) with GenBank accession number MW143047 was resolved in an unexpected phylogenetic position, as sister to the Pacific cupped oyster Magallana gigas (Thunberg, 1793) and share with this species three typical gene duplications that represent robust synapomorphies of the Magallana clade. In this study, we verified the identity of MW143047 using direct comparisons of single gene sequences, DNA barcoding and phylogenetic analyses. BLAST searches using as query each of the 12 protein coding genes (PCGs) and rRNA genes extracted from MW143047 retrieved M. gigas as best hit with 100% sequence identity for all genes. MW143047 is nested within the clade formed by M. gigas sequences, with virtually zero-length terminal branch, both in the cox1 gene tree (based on 3639 sequences) and in the 16S gene tree (based on 1839 sequences), as well as in the Maximum Likelihood mitogenomic tree based on concatenated sequence of 12 PCGs. Our findings suggest that the original specimen used for mitogenome sequencing was misidentified and represents an individual of M. gigas. This study reinforces the notion that morphological shell analysis alone is not sufficient for oyster identification, not even at high taxonomic ranks such as subfamilies. While it is well established that morphological identification of oysters should be validated by molecular data, this study emphasizes that also molecular data should be taxonomically verified by means of DNA barcoding and phylogenetic analyses. The implications of the publication of taxonomically misidentified sequences and mitogenomes are discussed.